Nitrogen and Stem Development: A Puzzle Still to Be Solved - Souza, Lucas Anjos; Tavares, Rafael (Frontiers in Plant Science, 2021)
High crop yields are generally associated with high nitrogen (N) fertilizer rates. A growing tendency that is urgently demanding the adoption of precision technologies that manage N more efficiently, combined with the advances of crop genetics to meet the needs of sustainable farm systems. Among the plant traits, stem architecture has been of paramount importance to enhance harvest index in the cereal crops. Nonetheless, the reduced stature also brought undesirable effect, such as poor N-uptake, which has led to the overuse of N fertilizer. Therefore, a better understanding of how N signals modulate the initial and late stages of stem development might uncover novel semi-dwarf alleles without pleiotropic effects. Our attempt here is to review the most recent advances on this topic.